1994
DOI: 10.1177/014572179402000305
|View full text |Cite
|
Sign up to set email alerts
|

Situational Obstacles to Adherence for Adolescents with Diabetes

Abstract: Twenty adolescents with insulin-dependent diabetes mellitus were interviewed to obtain samples of problem situations that create obstacles to dietary adherence. The resulting 57 situations were analyzed using a reliable coding system to determine the presence or absence of 28 stimulus features. A hierarchical cluster analysis was used to identify 10 relatively homogeneous categories of obstacles to dietary adherence: being tempted to stop trying; negative emotional eating; facing forbidden foods; peer interper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…These 2 subscales were derived from a previously validated scale of perceived barriers to diet and exercise in adults with T2DM 35 and from 2 other validated scales of perceived barriers in adolescents and adults with diabetes. 28,29 The internal reliability of the healthy eating barriers scale and exercise barriers scale in the current study was good (Cronbach's ␣ of .78, and .77, respectively).…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…These 2 subscales were derived from a previously validated scale of perceived barriers to diet and exercise in adults with T2DM 35 and from 2 other validated scales of perceived barriers in adolescents and adults with diabetes. 28,29 The internal reliability of the healthy eating barriers scale and exercise barriers scale in the current study was good (Cronbach's ␣ of .78, and .77, respectively).…”
Section: Methodsmentioning
confidence: 58%
“…Questions were selected and adapted from previously validated surveys of healthy and chronically ill adolescents, adolescents with T1DM, and adults with diabetes. [26][27][28][29][30][31][32][33][34] The majority of questions were close ended, but some open-ended questions were included to better ascertain adolescents' perceptions about barriers to selfcare behaviors. A series of open-ended questions asked adolescents what they thought was the hardest thing about checking blood sugars, performing exercise, following a diet, and other behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…An area of self-care barriers not well-studied in this population, but very relevant, are those related to the awareness of time, rushing, and planning. Several studies have found that time management, feeling pressured, or an unwillingness to take the time for self-care create barriers to adherence [2729]. …”
Section: Introductionmentioning
confidence: 99%
“…Many overweight and children and adolescents experience stress due to poor body image, low self- esteem, feelings of shame and embarrassment and other feelings of social isolation [17,18] Sharing their experiences with other children who have faced similar circumstances can lead to understanding, empathy, and mutual support. Peer support among individuals with the same chronic health problem is a powerful intervention because it combines the benefits of receiving and giving social support [1922].…”
Section: Discussionmentioning
confidence: 99%